BRS Vitória grapes with natural surfactant pretreatment: evaluation of mineral composition, physical-chemical characteristics, and sensory characteristics after raisin production - SHIMIZU-MARIN, Victoria Diniz; SILVA, Francielli Brondani da; GARCIA-SANTOS, Mariana de Souza Leite; JANZANTTI, Natália Soares; da SILVA, Roberto; LAGO-VANZELA, Ellen Silva Lago (Food Science and Technology, 2023)
Raisins have been gaining recognition for their nutrient and bioactive compound contents. Yet, pretreatments used for grape drying raise concerns regarding the economic viability and safety of the product. The objective of this proposal was to produce raisins from BRS Vitória grapes pretreated with a natural surfactant to accelerate the drying process. Subsequently, the influence of drying and pretreatment was evaluated for chemical composition (moisture, water activity (Aw), pH, total acidity (TA), reducing sugars (RS), and total sugars (TS)), total phenolic compounds (TPC), total anthocyanins, and qualitative and quantitative mineral composition. Finally, a sensory analysis of the raisins was conducted. By using the pretreatment, drying time decreased by approximately 38.5%. The raisins met the moisture requirements by the Brazilian and international regulations, and the pretreated raisins (PR) had a higher anthocyanin content, a high sugar concentration, acids, phenolic compounds (PC), and minerals (potassium (K), phosphorus (P), calcium (Ca), magnesium (Mg), and manganese (Mn)), and were well accepted by consumers, especially in terms of taste and appearance. Interestingly, the pretreatment also provided more brightness to the samples. In conclusion, BRS Vitória grapes yielded raisins with a complex composition, especially those that were subjected to the pretreatment, might be consumed as a healthier snack, adding PC and minerals to the diet.